A revolution in biotechnology (Cambridge University Press, 1989)
A Revolution in Biotechnology is an indispensable reference book on one of the most exciting and fast moving areas of modern science. The text is written by a team of leading figures in the field for non-specialist readers, and is illustrated throughout with diagrams and photographs, many in colour. We depend on living organisms for food, for medicines, and for a vast array of the chemicals that make modern life possible. A Revolution in Biotechnology tells how recent developments in basic research are leading not just to improvements in existing technology for producing these goods, but to a whole range of applications not previously thought possible.